CONTRASTING SOURCE COMPONENTS OF THE PALEOPROTEROZOIC SVECOFENNIAN METASEDIMENTS: DETRITAL ZIRCON U-PB, SM-ND AND GEOCHEMICAL DATA - Lahtinen R.; Huhma H.; Kousa J. (My University, 2002)
The Paleoproterozoic Svecofennian Orogen in the Fennoscandian shield can be regarded as one entity or as a collage of several accretionary units. To test for the possible occurrence of a suture zone dividing the Svecofennian Orogen into Central and Southern parts, we report new ion microprobe data on clastic zircons of nine samples of metasediments. Whole-rock Sm–Nd and geochemical data were acquired to characterize the source components of the metasediments. The Central Svecofennian metasediments in Finland can be divided to lower and upper types with inferred deposition ages at 1.92–1.91 and 1.90–1.88 Ga, respectively. Both types are immature and show a derivation from an unweathered orogenic source. The lower Central Svecofennian metasediments show a dominant Proterozoic age population at 1.93–2.02 Ga and a variation in εNd (1.9) values from about −3 to −0.5, which is mainly explained by variable amounts of Archean detritus (30–45%). The upper Central Svecofennian metasediments have εNd (1.9) at about 0, similar to values obtained from adjacent volcanic and plutonic arc rocks. One meta-arkose is tentatively classified as a molasse-type sediment with a source dominated by earlier Svecofennian sediments. Southern Svecofennian metasediments can be divided into mature and less mature types with dominant deposition ages at 1.90–1.88 Ga and εNd (1.9) values from −3 to +1. Mature quartzites seem to occur at least in two stratigraphic levels where the upper quartzites have maximum deposition ages at 1.87–1.86 Ga. A characteristic feature of some Southern Svecofennian metasediments is a dominant Proterozoic age population at 2.0–2.1 Ga. Coincident deposition of mature and immature sediments and volcaniclastic rocks indicate that different sources, weathered and non-weathered ‘basement’, and syn-depositional volcanic centers, produced simultaneously detritus to a large subsiding basin. Mature pelites and quartzites suggest a long residence time and stable passive margin or cratonic environment. The tectonic setting and possible provenance areas for the Central and Southern Svecofennian metasediments are also discussed. As a conclusion, the metasediments from the Central and Southern parts of the Svecofennian Orogen show different lithological characteristics and have contrasting source components. The presented isotope data indicate a different evolution of these parts prior to 1.89 Ga and the existence of a suture zone between them as proposed in earlier studies.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская